Analisis Pengaruh Disiplin Kerja, Beban Kerja, Lingkungan Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada PT.Smart Tbk Padang Halaban - Rahman, Fazrur; Broto, Bayu Eko; Pitriyani, Pitriyani (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the analysis of the influence of work discipline, workload, work environment and leadership style on employee performance at PT. SMART TBK Padang Halaban. Population and sample in this study are employees of PT.SMART TBK Padang Halaban as many as 45 people. This study uses work discipline, workload, work environment and leadership style as independent variables, while employee performance as a dependent variable. Data analysis in this study using the help of SPSS version 20. In individual/partial testing (t test), three variables have a significant influence and one variable that is not significant to employee performance. Where the value of the probability of siginifikan work discipline variable (X1) is less than 0.05 that is equal to 0.001 with the value of beta (acrylic) is equal to 0.406, for the variable workload (X2) is more than 0.05 that is equal to 0.076 with the value of beta (acrylic) of -0.212, work environment variable (X3) has a significant probability value of less than 0.05 that is equal to 0.014 with the value of beta (acrylic) of 0.276, as well as the variable leadership style has a significant probability value less than 0.05 is equal to 0.007 with a beta value of 0.582. For the results of the test analysis based on test F conducted shows that work discipline, workload, work environment and leadership style simultaneously or together have a positive significant influence on the performance of employees of PT SMART TBK Padang Halaban.